National Institute for Health and Clinical Excellence appraisal and ageism. Issue 5 (2nd January 2012) - Stevens, Andrew; Doyle, Nick; Littlejohns, Peter; Docherty, Mary
Abstract : The requirements of the UK Equality Act 2010 and some high profile criticism for using a potentially ageist methodology have prompted the National Institute for Health and Clinical Excellence (NICE) to assess the processes and methodology it uses to make appraisal decisions. This paper argues that NICE has established rigorous systems to protect against ageist decisions, has no track record of ageism and is well placed to meet the requirements of new UK equality legislation.